Osmanlı Düşüncesinde “Kriz” Kavrayışının Tarihsel Dönüşümü: İhtilal’den İnhitat’a - Okuyan, Hümeyra (Kutadgubilig, 2025)
Osmanlı Devleti insanlık tarihi içerisinde görkemli ve uzun olarak tarif edilebilecek bir tarihe sahiptir. Hüküm sürdüğü yıllar boyunca Osmanlı, tarihinin bazı dönemlerinde güçlü devlet olmanın yöntem ve araçlarına sahipken, bazı dönemlerinde iç ve dış kaynaklı krizlerle baş etmek zorunda kalan bir devlete dönüşmüştür. Bu krizlerin meydana geliş sebepleri dönemden döneme değişkenlikler gösterirken devletin bu krizleri alımlama, anlama, mukavele etme biçimleri arasında yöntemsel farklılıklar mevcuttur. Bu çalışma, Osmanlı düşüncesinde kriz kavrayışının XVI. yüzyıldan XIX. yüzyıla geçirdiği tarihsel dönüşümü, köken (arkhe) ve amaç (telos) üzerinden değerlendirmektedir. Osmanlı Devleti tarihinde kriz bilincinin öne çıktığı bu iki dönem başta krizin kökenine atfedilen unsur olmak üzere tarih, ıslahat ve insan anlayışı bakımından birbirinden ayrışmaktadır. XVI. yüzyılda “ihtilal” söylemiyle temsil edilen kriz kavrayışı, siyasal ve toplumsal düzende meydana gelen bozulmaları geçmişten sapma olarak yorumlayıp, “Kanun-i Kadim” ve “Nizam-ı Âlem” gibi yapılar aracılığıyla kökendeki düzene dönmeyi hedeflemiştir. XIX. yüzyıl ise klasik dönemin kriz kavrayışının beka için çare olamayacağı kabulü ile “inhitat” söylemini üretmiş; bu anlamda erken dönemin kriz kavrayışını da sorunsallaştırmıştır. Dolayısıyla inhitat söylemiyle birlikte krize bakışta “arkhe” ve “telos” da dönüşmüş, arayışlar geçmişin ihyasından geleceğin inşasına, döngüsel tarihten ilerlemeci tarih anlayışına, mesul bürokrasiden mükellef vatandaşa dönüşmüştür. Bu saikle çalışma, Osmanlı düşüncesinde iki dönem arasında dönüşen kriz kavrayışıyla birlikte köken ve amaca atfedilen unsurların da değiştiği ve krizin bir karar anı olarak doğurduğu tarihsel sonuçlara ulaşmaktadır.

The Ottoman Empire possesses a history that may be described as both magnificent and extensive within the broader course of human history. Throughout its reign, the Empire at times possessed the methods and means of being a powerful state, while at other times, it was transformed into a state forced to contend with internal and external crises. Although the causes of these crises varied from period to period, the ways in which the state perceived, comprehended, and responded to these crises differed methodologically. This study evaluates the historical transformation of the Ottoman conception of crisis from the 16th to the 19th century through the notions of origin (arkhe) and purpose (telos). These two periods, in which crisis consciousness came to the fore in Ottoman history, differ fundamentally in their understandings of history, reform, and the human being—most notably in the elements attributed to the origin of the crisis. The 16th-century crisis conception, represented by the discourse of “ihtilal” (injury), interpreted disruptions in the political and social order as deviations from the past and sought to restore the original order through structures such as “Kanun-i Kadim” and “Nizam-ı Âlem”. In contrast, the 19th century produced the discourse of “inhitat” (decline) by acknowledging that the classical conception of crisis could no longer serve as a remedy for the state’s survival, thereby problematizing the early period’s understanding of crisis. Consequently, with the emergence of the inhitat discourse, the notions of arkhe and telos in crisis perception were transformed: quests shifted from the revival of the past to the construction of the future, from a cyclical conception of history to a progressive one, and from a responsible bureaucracy to a dutiful citizenry. Accordingly, this study concludes that the transformation in crisis perception between the two periods in Ottoman thought also entailed a change in the elements attributed to origin and purpose, ultimately revealing the historical consequences generated by crisis as a moment of decision.
The Historical Transformation ff The Concept Of “Crisis” in Ottoman Thought: From Ihtilal to Inhitat
Keywords: Osmanlı Düşüncesi; Kriz; İhtilal; İnhitat; Arkhe; Telos; Islahat; Ottoman Thought; Crisis; Disruption; Decline; Origin; Purpose; Reform